Repertoires and geographical variation in song of oriental magpie robin (Copsychus saularis) in northern Thailand - Danmek A. (2017)
The relation of geographical variation of magpie song to study area, can show obvious degree of similarities and differences in the structure of the song. Spectrogram studies revealed that all song types shared some common features. The frequency range of song was fixed between 1.99 and 5.57 kHz. A basic strophe (syllable) and a climax strophe are synthesized to form a complete song. It was found that songs were always introduced by repeating a basic strophe followed by a climax strophe and terminating with the basic strophe. A strophe contains one or more core elements. The last core element is referred to as the marking element, which is followed by a fine structure of specific elements. Discriminant function analysis revealed that the mean length of strophe (MLSt), the mean length at terminal part of strophe (MLTPSt), the number of element at the terminal part of strophe (NETPSt) and the number of element in strophe (NESt) were found to be the best determinants for differentiating song structure and classifying it into eight study sites. The geographical isolation and long distance of the study site, allowed birds to learn and produce song variations. This variation of song structure can show the unique characteristic of songs in each study area as well.